2020
DOI: 10.3389/fphar.2020.00955
|View full text |Cite
|
Sign up to set email alerts
|

Simiao Decoction Alleviates Gouty Arthritis by Modulating Proinflammatory Cytokines and the Gut Ecosystem

Abstract: Simiao decoction, a classical traditional Chinese medicine (TCM) formula, has been widely used for thousands of years due to its safety and efficiency in treating gouty arthritis. Utilizing serum proinflammatory cytokines and gut ecosystems, this study elucidated the mechanisms of alleviating gouty arthritis by Simiao decoction. Simiao decoction (4.0, 8.0, and 16.0 g/kg) was orally administered to gouty arthritis mice and febuxostat was given as a positive control. The spleen, kidney, and liver indexes indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 52 publications
1
49
0
2
Order By: Relevance
“…In addition to clinical studies, experimental studies have also suggested the urate lowering effects of Simiao Pills, which act on xanthine oxidase (XO), uric acid transport-related proteins urate anion transporter 1 (URAT1) and glucose transporter 9 (GLUT9), and also modulate the inflammation, oxidative stress and other processes ( Hu et al, 2010 ; Hua et al, 2012 ; Shi et al, 2013 ; Pan et al, 2014 ; Ma et al, 2015 ; Lin et al, 2020 ). The finding suggests that Chinese herbal medicines are mostly multi-targeted or have interplay with other signaling pathways to lower sUA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical studies, experimental studies have also suggested the urate lowering effects of Simiao Pills, which act on xanthine oxidase (XO), uric acid transport-related proteins urate anion transporter 1 (URAT1) and glucose transporter 9 (GLUT9), and also modulate the inflammation, oxidative stress and other processes ( Hu et al, 2010 ; Hua et al, 2012 ; Shi et al, 2013 ; Pan et al, 2014 ; Ma et al, 2015 ; Lin et al, 2020 ). The finding suggests that Chinese herbal medicines are mostly multi-targeted or have interplay with other signaling pathways to lower sUA levels.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] The findings of Lin suggested that simiao decoction was an effective therapeutic drug for GA and the gut ecosystem might act as a potential anti-inflammatory target of Simiao powder. [ 21 ] Qiu found that simiao powder can significantly improve the symptoms and signs of GA and decrease the levels of UA and CRP. [ 22 ] However, no reports of comparisons simiao powder and acupuncture on GA has been found.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have supplied insights into novel treatment strategies and approaches for liver fibrosis. For example, the Simiao decoction can reduce inflammatory factor secretion and regulate intestinal flora homeostasis (91). Additionally, a TCM formula was found to reverse increases in scleroderma and Proteobacteria caused by a high-fat diet, resulting in a decreased scleroderma to Bacteroides ratio and an increased abundance of Bacteroides (92).…”
Section: Summary Of the Effects Of Tcm On Liver Fibrosis Through The mentioning
confidence: 99%